Research on the impact of digital inclusive finance on rural human capital accumulation: A case study of China - Li, Hanjin; Zhuge, Ruiyang; Han, Jin; Zhao, Peng; Gong, Maogang (Frontiers in Environmental Science, 2022)
The accumulation of rural human capital is one of the important factors to realize the sustainable development of the rural economy. Digital inclusive finance eases the budget constraints of farmers and affects their willingness and ability to invest in education which improves human capital accumulation. The impact of digital inclusive finance on rural human capital accumulation is strong but complex to determine. Based on the data from 31 provinces of China from 2011 to 2020, this study uses the systematic Generalized Moment Method (GMM) to build an analytical framework to explore the impact mechanism and differences of digital inclusive finance over the rural human capital accumulation regional levels. The study found that with the development of digital inclusive finance and the expansion of the breadth of coverage, and usage of digital inclusive finance can significantly enhance the accumulation of rural human capital. In terms of regional differences, the boosting effect of digital inclusive finance on rural human capital accumulation is greater in the Northeast than that in the Central, Western and Eastern regions of China. The impact of the extent of digital inclusive finance coverage on rural human capital accumulation is significantly greater in Northeast and Eastern regions than in Central and Western regions; the impact of the depth of digital inclusive finance usage on rural human capital accumulation is limited in Central China. Its findings and results can help to further develop digital inclusive finance, particularly for human capital accumulation in rural areas.